Efektivitas Model Problem-Based Learning Berbantuan Video Pada Mata Pelajaran Dasar Listrik dan Elektronika - Permadi Putra; Dwiprima Elvanny Myori (Jurnal Pendidikan Teknik Elektro, 2023)
This study aims to determine the effectiveness of the video-assisted Problem-Based Learning model as a learning model in the subject of Basic Electrical and Electronics class X TITL at SMK Negeri 5 Padang. Learning theory, especially in learning measuring instruments and electrical test equipment, problems are often found in the process of measuring and reading measuring instruments. Problem-based learning is very suitable for use in this study so that students are accustomed to solving possible problems that occur in everyday life with the use of measuring instruments. This study uses a quantitative approach with a quasi-experimental method with a one-group pretest and posttest design. The object of this research is Problem-Based Learning and the effectiveness of video-assisted Problem-based learning on learning outcomes in the basic subjects of electricity and electronics. The subjects in this study were students of class X TITL 1 SMKN 5 Padang. The research instrument used was in the form of pretest and posttest questions in the form of objective questions. Based on the posttest average score is in the high category. Therefore, the application of the video-assisted Problem-Based Learning model as a learning model in the basic subjects of electricity and electronics is said to be effective because the classical value and effect size are in the high category.